2015
DOI: 10.1111/jai.12785
|View full text |Cite
|
Sign up to set email alerts
|

Reproductive traits of shovelnose sturgeon Scaphirhynchus platorynchus (Rafinesque, 1820) in the lower Platte River, Nebraska

Abstract: Summary We assessed reproductive status, fecundity, egg size, and spawning dynamics of shovelnose sturgeon Scaphirhynchus platorynchus in the lower Platte River. Shovelnose sturgeon were captured throughout each year during 2011 and 2012 using a multi‐gear approach designed to collect a variety of fish of varying sizes and ages. Fish were collected monthly for a laboratory assessment of reproductive condition. Female shovelnose sturgeon reached fork length at 50% maturity (FL50) at 547 mm and at a minimum leng… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(12 citation statements)
references
References 46 publications
0
12
0
Order By: Relevance
“…These are minimum estimates because even though a fish might be spawning every year, our sampling could have missed them in some years, giving the false appearance of a multi-year return time for spawning. Our finding of large proportions of shovelnose sturgeon possibly spawning annually, including at least one female, is unusual; previous studies from other populations have consistently reported that most shovelnose sturgeon do not spawn every year, with a spawning periodicity of 2-5 years for females and 1-2 years for males (Keenlyne, 1997;Tripp et al, 2009;Hamel et al, 2015a). Several of these studies have examined gonad characteristics during the spring spawning period to document actual spawning by individuals.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…These are minimum estimates because even though a fish might be spawning every year, our sampling could have missed them in some years, giving the false appearance of a multi-year return time for spawning. Our finding of large proportions of shovelnose sturgeon possibly spawning annually, including at least one female, is unusual; previous studies from other populations have consistently reported that most shovelnose sturgeon do not spawn every year, with a spawning periodicity of 2-5 years for females and 1-2 years for males (Keenlyne, 1997;Tripp et al, 2009;Hamel et al, 2015a). Several of these studies have examined gonad characteristics during the spring spawning period to document actual spawning by individuals.…”
Section: Discussionmentioning
confidence: 99%
“…Under this explanation, extremely long lifetimes need not be invoked to account for large size. Data on size and age at maturation from shovelnose sturgeon from the Middle Mississippi River in Missouri/Illinois, and the Platte River, Nebraska, support this idea and indicate that whereas the smallest and youngest mature fish were on the order of 450-500 mm FL and ages 4-7 and that most fish had matured by about 600-650 FL and ages 10-12, some fish did not mature until 700-750 mm FL and ages 13-18 (Tripp et al, 2009;Hamel et al, 2015a). This variation nearly encompasses the range of size and ages we found in mature shovelnose sturgeon in the LWR.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Beluga sturgeon Huso huso (Linnaeus) was reported to have a relative fecundity between 2750 to 10,500 eggs per kg body weight (Raspopov 1987), while white sturgeon ranged from 3192 to 8582 with a mean of 5648 eggs per kg body weight (Chapman et al 1996). Smaller bodied sturgeon species have been reported to produce more eggs per kg body weight with shortnose sturgeon (A. brevirostrum) having an average relative fecundity of 11,568 (Dadswell 1979), while shovelnose sturgeon, in the local proximity of our study, had 18,355 eggs per kg body weight in the Platte River (Hamel et al 2015).…”
Section: Discussionmentioning
confidence: 53%
“…The initial location of each sturgeon was randomly assigned to a cell with nonextreme water velocity (≤0.6 m/s) and depth (≥0.5 m). The initial age structure follows a Poisson distribution with mean age of 7, which is truncated at a maximum age of 16 based on field observations (Hamel, Rugg, Pegg, Patiño & Hammen, 2015), and the initial sex ratio is 1:1. Sex is randomly assigned to each fish, assuming a binomial distribution.…”
Section: Methodsmentioning
confidence: 99%